Costume Irui (2021)
This research is a development of the Otaku youth culture in the city of Cali in relation to the wardrobe, developing their identity through clothing. To define the identity of the Otaku wardrobe we have considered four phases, an investigation, an observation, an understanding and a use of design tools; in order to solve a problem that attacks the Cali market and the otaku youth culture. To understand being otaku on the outside we have relied on knowledge in the field of costume design, evidencing the information that costumes can provide in representation of a culture, the same information that will be used to give the Cali market a new proposal of identity for this culture.